WAKTU PUASA ARAFAH PERSPEKTIF MUHAMMAD BIN SHALIH AL ‘UTSAYMIN: Telaah Kajian Hukum Islam dan Astronomi Islam - Afwadzi, Benny; Alifah, Nur (ULUL ALBAB Jurnal Studi Islam, 2017)
All this time there was a different opinion about the time for Arafah fasting. Whether to comply with the provisions of Saudi Arabia or adjust the territory of each person. In Saudi Arabia, there appears a mufti named Muhammad bin Shalih al ‘Utsaymin who holds that fasting of Arafah must follow the country where a person lives. This opinion is interesting because it is different from other Salafis, such as ‘Abd al ‘Aziz bin Baz, Abdul Hakim bin Amir Abdat and HTI. Using the analytical tools of Islamic law and Islamic astronomy, the authors conclude that the fatwa issued by al ‘Utsaymin is considered quite representative, because considering the locality of a country, realizing the time of worship should adjust the kamariyah time of the country, and also in accordance with the mathla‘ in the form of mathla‘ wilayah al hukmi. Opinions as expressed by al ‘Utsaymin is conformable with the implementation of the time of the fasting of Arafat by the majority of Muslims in Indonesia.